HUBUNGAN PELAKSANAAN METODE KOMUNIKASI: SITUATION, BACKGROUND, ASSESMENT, RECOMENDATION (SBAR) SAAT TIMBANG TERIMA TUGAS KEPERAWATAN DENGAN KEPUASAAN KERJA PERAWAT DI RUANG RUANG RAWAT INAP RSUD SOLOK - Isna Ovari (LPPM UNIVERSITAS PERINTIS INDONESIA, 2015)
Situation, Backround, Assesment, Recomendation (SBAR)communication is communication techniques provided the framework for health workers to deliver the patient's condition (Permanente, K. 2011). Inaccuracies of information can cause serious impact on patients, nearly 70% of events that result in death or serious injury in the hospital due to poor communication. This study aimed to determine the relationship of the implementation of the SBAR communication weigh thank duty nursing job satisfaction of nurses This study was conducted from 19 to 29 January 2015 in Room Inpatient Hospital Solok. The research sample 58 nurses in the inpatient unit interne men, children and surgical lung in Solok District Hospital in 2015 with a total sampling and tested by chi square. Results of univariate known 53.4%, implementation of the SBAR communication weigh patients received 51.7% did not materialize and job satisfaction of nurses expressed less satisfaction. Results of bivariate significant relationship between the implementation of SBAR communication and job satisfaction of nurses in patient wards of hospitals in 2015 (p = 0.000, OR = 29,000). Hope researchers, nurses in Solok expected Inpatient Hospital SBAR communication to avoid causing injury or serious problem in patients due to inaccurate information. In addition it is expected that the hospital in order to provide SBAR communication training for all nurses know and understand about the SBAR communication.